Primary Hyperparathyroidism in Patients with Multiple Endocrine Neoplasia Type 1 - Grzegorz Piecha; Jerzy Chudek; Andrzej Więcek (International Journal of Endocrinology)
Primary hyperparathyroidism may occur as a part of an inherited syndrome in a combination with pancreatic endocrine tumours and/or pituitary adenoma, which is classified as Multiple Endocrine Neoplasia type 1 (MEN-1). This syndrome is caused by a germline mutation in MEN-1 gene encoding a tumour-suppressor protein, menin. Primary hyperparathyroidism is the most frequent clinical presentation of MEN-1, which usually appears in the second decade of life as an asymptomatic hypercalcemia and progresses through the next decades. The most frequent clinical presentation of MEN-1-associated primary hyperparathyroidism is bone demineralisation and recurrent kidney stones rarely followed by chronic kidney disease. The aim of this paper is to present the pathomechanism, screening procedures, diagnosis, and management of primary hyperparathyroidism in the MEN-1 syndrome. It also summarises the recent advances in the pharmacological therapy with a new group of drugs—calcimimetics.